2015
DOI: 10.3835/plantgenome2014.07.0028
|View full text |Cite
|
Sign up to set email alerts
|

Faba Bean: Transcriptome Analysis from Etiolated Seedling and Developing Seed Coat of Key Cultivars for Synthesis of Proanthocyanidins, Phytate, Raffinose Family Oligosaccharides, Vicine, and Convicine

Abstract: Faba bean (Vicia faba L.) has been little examined from a genetic or genomic perspective despite its status as an established food and forage crop with some key pharmaceutical factors such as vicine and convicine (VC), which provoke severe haemolysis in genetically susceptible humans. We developed next-generation sequencing libraries to maximize information to elucidate the VC pathway or relevant markers as well as other genes of interest for the species. One selected cultivar, A01155, lacks synthesis of the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 35 publications
(43 reference statements)
1
17
0
Order By: Relevance
“…1 ). A fragment of this gene, mis-annotated as reticuline oxidase-like , was previously identified among five other gene fragments based on gene expression comparison between normal- and low-vicine and convicine cultivars 11 . More recently, Khazaei et al (2017) 12 showed that a SNP coding for a silent mutation within this fragment distinguished between normal- and low-vicine and convicine cultivars in a diversity panel of 51 faba bean accessions.…”
Section: Main Textmentioning
confidence: 99%
“…1 ). A fragment of this gene, mis-annotated as reticuline oxidase-like , was previously identified among five other gene fragments based on gene expression comparison between normal- and low-vicine and convicine cultivars 11 . More recently, Khazaei et al (2017) 12 showed that a SNP coding for a silent mutation within this fragment distinguished between normal- and low-vicine and convicine cultivars in a diversity panel of 51 faba bean accessions.…”
Section: Main Textmentioning
confidence: 99%
“…This study provided a useful snapshot of the functional classification and relative expression level of more abundant transcripts from the embryo transcriptome in the early to middle stages of its development. Subsequently, studies began to encompass multiple, separate inbred genotypes (Webb et al., ), as well as multiple tissues and genotypes (Ray, Bock, & Georges, ). The deepest transcriptome coverage produced has come from Illumina sequencing of a library of mixed tissues enriched with embryo transfer cells (Zhang et al., ).…”
Section: Genomicsmentioning
confidence: 99%
“…Several transcriptome datasets have been previously generated for faba bean, from the cultivars Windsor [53], Icarus and Ascot [22], CDC Fatima, SSNS-1, and A01155 [39], Fiord [40,54], INRA-29H and Vf136 [42], BPL10 and Albus [29], and Wizard [43]. These datasets were generated from a selection of tissues including root, shoots, seedling, embryo, seed coat, leaves, or mixed tissues.…”
Section: Annotation Of the Transcriptome Assembliesmentioning
confidence: 99%